"Stigma and HIV Are Like Brother and Sister!": The Experience of African-Born Persons Living with HIV in the US - Alina Cernasev; William L. Larson; Cynthia Peden-McAlpine; Todd Rockwood; Paul L. Ranelli; Olihe Okoro; Jon C. Schommer (MDPI AG, 2020)
Minnesota has seen an increase in the number of immigrants from Africa, notably in the mid-1990s, making up around 2% of Minnesota's total population. This population also faces many impediments that cause important difficulties not only for HIV prevention but also for treatment and care options. The objectives of this study were to capture the experiences of Persons Living with HIV (PLWH) in Minnesota (US) and to elicit their stories about their diagnosis news and what management strategies they use for coping with the stigma associated with the disease. Participants were recruited via fliers in pharmacies, clinics, and HIV service centers located in Minnesota. Recruitment continued until thematic saturation was obtained. Fourteen subjects participated in audio-recorded, semi-structured interviews that were transcribed verbatim into written text. The transcriptions were analyzed using Thematic Analysis. Three themes emerged from the data. Theme 1: Cruel News: "HIV-Oooooo! I wish I was dead", Theme 2: This is My Secret! and Theme 3: "Stigma and HIV are brother and sister". The results demonstrate that stigma is an ever-present problem in African-born PLWH living in the US. Participants perceived the stigma associated with HIV status to affect their lives and culture at individual, familial, and societal levels.